Utilization and Satisfaction to Activities Media of the To Be Number One Project of Youth in Bangkok - Kachentaraphan, Paiboon; BOONSONG, PARINYAR; Thongrin, Santat; Choonwijitra, Wasan (Journal of Health Science of Thailand, 2025)
The objectives of this research were to study Bangkok youths’ (1) utilization of the To Be Number One project’s media activities; (2) their satisfaction with those media activities; (3) the youths’ utilization of the media activities when compared by demographic factors; (4) the youths’ satisfaction with the media activities when compared by demographic factors; and (5) the relationship between youths’ utilization of the media activities and their satisfaction with the media activities. This was survey research. The sample population consisted of 450 young people studying at educational institutions in Bangkok who were members of the To Be Number One project, who were chosen by stratified random sampling. The research instrument was a questionnaire. Data were statistically analyzed using frequency, percentage, mean, standard deviation, t test, ANOVA and Pearson’s correlated co-efficient. The results showed that (1) overall, the samples utilized the To Be Number One media activities to a high degree. They used the creative activities for entertainment and relaxation the most, and secondarily to talk about the things they learned from the activities with their friends and acquaintances. (2) Overall, the samples had a high level of satisfaction with the To Be Number One media activities. The highest satisfaction scores were for the presentation format of the activities. (3) Youths from different grade levels and who had different grade point averages, income range of their parents or guardians, and different frequency of joining in To Be Number One activities had different utilization of the activities to a statistically significant degree at the levels of 0. 05 and 0. 01. (4) Youths of different ages, from different grade levels, with different income ranges of their parents or guardians, and who had different frequency of joining in To Be Number One activities had different levels of satisfaction with the activities to a statistically significant degree at the levels of 0. 05 and 0. 01. (5) Bangkok youths’ utilization of the To Be Number One media activities was correlated with their level of satisfaction with the content and pattern of the media activities overall and in terms of the clarity of the content and the credibility of the content activities to a statistically significant degree at the level of 0. 01. Keywords: Activity media, Satisfaction, To Be Number One Project, Utilization